THE DIFFICULTIES DURING TEACHING PRACTICE OF PROSPECTIVE MATHEMATICS TEACHER - Stevi Natalia (Adisam Publisher, 2024)
This study aims to reveal the phenomenon of difficulties experienced by prospective mathematics teachers in carrying out teaching practice, which are focused on difficulties in using mathematics learning media. The method used in this research is descriptive qualitative. Through questionnaires to collect data on the difficulties of prospective teachers during teaching practice, it was found that the difficulty in using the right media was the highest difficulty than others. Data collection techniques to dig deeper into the reasons for the difficulties experienced by students in determining the right learning media were carried out using interviews. The reasons for the difficulties of prospective teacher in using learning media are 1). The habit of teachers teaching mathematics at the school who do not use learning media causes students to have difficulty making decisions in choosing the appropriate media used and hesitate, 2). Limited school infrastructure facilities. 3). Lack of information sources to help prospective teachers choose the right media, in this case, the lack of role of teaching practice supervisors and mentor teachers.